2017
DOI: 10.1002/eat.22735
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and eating disorder pathology

Abstract: This is the first study to assess the full spectrum of ED pathology in a low-income, marginalized population with food insecurity. Given that food insecurity is a global concern, results from this study suggest that greater attention to the association between ED pathology and food insecurity is warranted by researchers around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 25 publications
(37 reference statements)
14
159
4
3
Order By: Relevance
“…Seven studies have examined the relationship between WBI and other outcomes related to weight and health. These studies reported the following findings: WBI was lower among white adults with (versus without) a family weight history of overweight/obesity ; higher WBI was associated with a younger age of onset of overweight/obesity and reports of food insecurity ; and WBI was not significantly related to television use , health care utilization or alcohol consumption .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies have examined the relationship between WBI and other outcomes related to weight and health. These studies reported the following findings: WBI was lower among white adults with (versus without) a family weight history of overweight/obesity ; higher WBI was associated with a younger age of onset of overweight/obesity and reports of food insecurity ; and WBI was not significantly related to television use , health care utilization or alcohol consumption .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, conducted with different participant groups in the US, reported that food insecurity was associated with binge eating (Becker et al, ; Bruening et al, ) and was unexpectedly associated with weight‐compensatory behaviors (Becker et al, ). Our previous study extended this new emerging literature by finding that low and very low food securities were significantly associated with both BED and obesity versus a healthy‐weight comparison group (Rasmusson et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…We recently reported, in a survey study of 1,251 US adults, that food insecurity was associated with BED and obesity (without comorbid eating disorders; Rasmusson, Lydecker, Coffino, White, & Grilo, ). A previous study of 503 adults seeking food from food pantries reported that food‐insecurity severity was associated with binge‐eating frequency, eating‐disorder psychopathology, and compensatory‐behavior frequency (vomiting, laxative/diuretic use, and excessive exercise; Becker, Middlemass, Taylor, Johnson, & Gomez, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Community-based participatory research (CBPR) disrupts traditional research power hierarchies in which participants simply provide data to researchers, and better ensures that interventions meet the needs of communities. For example, CBPR has been credited as essential to the success of the global dissemination of an evidencebased eating disorder prevention program(Becker, Middlemass, Taylor, Johnson, & Gomez, 2017). In this issue,Ciao, Ohls, and Pringle (2018) provide a further case example of CBPR research in action.…”
mentioning
confidence: 99%